"Blindly" ADA Dose Escalation to 80 mg Weekly in Crohn's Disease Patients with LOR: Is It Cost Effective or Not?. Issue 11 (November 2015) - Sartini, Alessandro; Di Girolamo, Maria; Bertani, Angela; Villa, Erica
Abstract : Article first published online 29 September 2015.